2018
DOI: 10.1021/acs.jmedchem.8b00714
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography (PET) Ligand Development for Ionotropic Glutamate Receptors: Challenges and Opportunities for Radiotracer Targeting N-Methyl-d-aspartate (NMDA), α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA), and Kainate Receptors

Abstract: Ionotropic glutamate receptors (iGluRs) mediate excitatory neurotransmission within the mammalian central nervous system. iGluRs exist as three main groups: N-methyl-d-aspartate receptors (NMDARs), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs), and kainate receptors. The past decades have witnessed a remarkable development of PET tracers targeting different iGluRs including NMDARs and AMPARs, and several of the tracers have advanced to clinical imaging studies. Here, we assess the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 190 publications
1
33
0
Order By: Relevance
“…A recent study using a tracer for the metabotropic glutamate receptor 5 found no patient‐control differences. New tracers are under development, but lack of specificity remains an ongoing problem when attempting to image glutamate receptors.…”
Section: Glutamatementioning
confidence: 99%
“…A recent study using a tracer for the metabotropic glutamate receptor 5 found no patient‐control differences. New tracers are under development, but lack of specificity remains an ongoing problem when attempting to image glutamate receptors.…”
Section: Glutamatementioning
confidence: 99%
“…As such, the glutamate receptors present a diverse range of important targets for molecular brain imaging by single photon emission computed tomography (SPECT) and positron emission tomography (PET). While there have been several reviews of this topic in recent years [ 20 , 21 , 22 , 23 ], we now present a systematic review of the state of development of glutamate receptor imaging, placing our emphasis on the findings of clinical studies, and on the lacunae remaining in the literature due to lack of specific tracers for many of these molecular targets. In selected cases, we give an account of the procedures for radiopharmaceutical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Subtype‐selective allosteric modulators of the NMDA receptor bind to allosteric sites, which are distinct from the competitive binding sites and allow pharmacological and therapeutic interventions . Triggered by the discovery of traxoprodil, a noncompetitive antagonist for the GluN2B‐containing NMDA receptors with rapid antidepressant‐like effects, enormous effort has been put into the development of GluN2B selective ligands including radioligands for positron emission tomography (PET) imaging over the last decades . However, there is a striking lack in comprehending and monitoring subunit‐selective modulations other than of GluN2B.…”
Section: Introductionmentioning
confidence: 99%